Does transformational leadership foster innovative work behavior? The roles of psychological empowerment, intrinsic motivation, and creative process engagement - Bin Saeed, Bilal; Afsar, Bilal; Shahjehan, Asad; Imad Shah, Syed (Economic research - Ekonomska istraživanja, 2019)
This study examines how transformational leadership relates to employee's innovative work behavior through intrinsic motivation, psychological empowerment, and creative process engagement. On the basis of an interactional approach, this study hypothesized that (a) there is an interaction between transformational leadership, intrinsic motivation, and psychological empowerment, such that transformational leadership has the strongest positive relationship with innovative work behavior when employees have high levels of intrinsic motivation and psychological empowerment; and (b) creative process engagement mediates the effect that this three-way interaction between transformational leadership, intrinsic motivation, and psychological empowerment has on innovative work behavior. In Study 1, we used a time-lagged research design, collecting multi-source data from 347 software engineers and their respective supervisors, working in IT companies in China. The results of Study 1 supported our hypotheses. In Study 2, we used a more temporally rigorous research design in which data were collected in three stages, with a six-month time interval separating Stages 1 and 2, and Stages 2 and 3. On the basis of the time-lagged and multi-source data from 393 software engineers and their respective supervisors, from IT companies in Pakistan, we found that Study 2 produced the same results as Study 1.